1 - Genealogies of Coloniality and Implications for Africa’s Development - Ndlovu-Gatsheni, Sabelo J. (Africa Development, 2021)
How Africa was conceived as an idea and integrated into the evolving Euro-North American-centric modernity is a tale of genealogies of colonialities and African resistance(s). Genealogies of coloniality span eight broad and overlapping epochs in the production of Africa that impinged on its development in various direct and indirect ways. The eight epochs distilled are the paradigm of discovery and mercantilist order running from the fifteenth century to the eighteenth century dominated by the slave trade and mercantilism; the post-1648 Westphalian order that inaugurated the exclusion of Africa from sovereignty; the 1884-5 Berlin consensus, scramble for and conquest of Africa that concretised the dismemberment and fragmentation of Africa; colonial governmentality that was characterised by production of African colonial subjectivity; the post-1945 United Nations decolonisation normative order that amounted to the accommodation of Africa to the lowest echelons of the modern world system; the Cold War coloniality that polarized Africa ideologically and reduced it to a theatre of proxy hot wars; the post-Cold War triumphalism of neoliberal order that Francis Fukuyama (1992) articulated as ‘the end of history and the last man’; the post-9/11 anti-terrorist order that produced a new securitization order; and the current coloniality of markets and new scramble for Africa. The article posits that African development’s trials and tribulations are deeply embedded within these overlapping epochs that were accompanied by epistemicides, genocides, usurpations, appropriations and disruptions. Africa is today still struggling to free itself from the constraining global colonial matrices of power that have been in place since the time of colonial encounters.